Comparison of High Flex Posterior Stabilized Implant (PS TKR) and Medial Pivot Implant (MP TKR) in Total Knee Arthroplasty with Respect to Knee Range of Motion, A Short Term Study - Ali Raza Shah, Sohail Hafeez, Sana Farid Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Osteoarthritis of the knee is the most common cause of functional impairment in the elderly. A complete knee arthroplasty is the most common knee operation for patients with advanced osteoarthritis. A complete knee arthroplasty is a surgical procedure that is used to treat osteoarthritis in its most severe form." Rheumatoid arthritis, advanced degenerative arthritis, and other forms of this type of osteoarthritis fall under this category. This way of treating different types of arthritis is both highly successful and completely risk-free. MP-TKR and PS-TKR designs have been proven to be beneficial only through a little amount of research so far. So, the aim of this study was to compare the mean range of motion by using two different types of implants i.e. high flexed posterior stabilized implant and medial pivot implant. Objectives: To compare the mean range of motion, in patients with advanced arthritis, treated with total knee arthroplasty, by using two different types of implants i.e. high flexed posterior stabilized implant and medial pivot implant. Study design: It is Randomized Comparative Trial. Setting: Department of Orthopedic Surgery at Shifa International Hospital, Islamabad. Subjects: A total of 62 patients were included in our study, which is divided into 2 groups, comprising of 31 patients in each group. Methods: The hospital's ethical review committee gave permission to this research, so it could proceed. These patients was kept in two groups on the basis of implant used i.e. PS TKR group and MP TKR group. Patient demographics and clinical history was taken by the principal investigator. All patients was undergo total knee replacement surgery using either posterior stabilized implants or medial pivot implants. All surgeries was performed by experienced orthopaedic surgeons having experience from 10 years to 30 years. Patients was discharged from hospital at 5th postoperative day after change of dressing and was called for follow up at 2 weeks during which post-operative knee range of motion was assessed. Knee range of motion was measured using goniometer with patients supine. The patient's data was analyzed with SPSS Version 23, a statistical software package for social sciences. For quantitative data, we utilized mean standard deviations, while for qualitative data, we used frequencies. If the probability was less than 0.05, it was significant. Results: The mean age of the patients in PS TKR was 66.35 ± 6.21 and in MP TKR was 64.74 ± 5.35. In our study 24 (38.7 %) were male and 38 (61.3 %) were female. The pre-operative ROM in PS TKR was 112.71 ± 1.79 and in MP TKR implant was 120.52 ± 1.46. The post-operative ROM in PS TKR implant was 109.13 ± 0.81 and in MP TKR was 109.00 ± 0.82. There is no significant difference in post-operative ROM in between the implant (PS TKR and MP TKR) as the p value is less than level of significance. Conclusions: We concluded that there is no difference in post-operative range of motion in patients who have undergone PS-TKR or MP-TKR.